Phylogenetic Analysis of the Relationship Between Puma Concolor and the Genus Panthera Within The Family Felidae Based on the COI Gene - Luthfiah Nurfajriyah; Mayla Maulida; Fadhil Muharram; Nifrah Mislah; Topik Hidayat (Tropical Genetics, 2026)
Puma concolor exhibits morphological similarities to large cats of the genus Panthera, which often lead to ambiguity in assessing its phylogenetic relationships. This study aimed to analyze the phylogenetic position of Puma concolor within the family Felidae using the mitochondrial gene Cytochrome Oxidase Subunit I (COI). Phylogenetic analyses were conducted on 28 Felidae species with three outgroup species using MEGA4 and PAUP*. The results showed that Puma concolor is clearly separated from the Panthera clade and occupies an independent phylogenetic position, supported by bootstrap values as well as Consistency Index and Retention Index values greater than 0.50. These findings confirm that the morphological similarities between pumas and large cats are the result of convergent evolution and support the classification of Puma concolor within the subfamily Felinae.